(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The communication of the Soatobaru village government in the implementation of development was important among all parties involved in the village development effort, especially between the village government and the community. Dissemination of development information that has been carried out until now is carried out through communication media from communicators to communicants, both those handled by the village government and the media. In the concept of communication, a communicator here plays a very important role, why? Because a Communicator must have good communication skills so that a communicant can capture messages quickly and accurately. In implementing village development for village-scale local authority, the village government needs to carry out development stages which include; Planning, Budgeting, Implementation, Reporting, Monitoring and Monitoring. Reliable indicators are knowledgeable communicators. The purpose of village development, as stated in Law No. 6 of 2014 concerning Villages, is to improve human welfare and reduce poverty through the provision of basic needs, development of village facilities and infrastructure, development of local economic potential and sustainable use of natural and environmental resources. Keywords: Communication, Village Government, Planning, Development